1995
DOI: 10.1111/1523-1747.ep12612786
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinases-1 Is Decreased and Activated Gelatinases Are Increased in Chronic Wounds

Abstract: The balance between matrix deposition and tissue turnover is fundamental in wound healing. It is likely that the balance between proteolytic enzymes and their inhibitors contributes to this balance. Matrix metalloproteinases are clearly important in tissue turnover, but their roles in wound healing are poorly understood. To investigate this, fluid from healing wounds resulting from mastectomies was collected from 1 h to 10 d post-surgery, and was analyzed for tissue inhibitor of metalloproteinases-1 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
4
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(198 citation statements)
references
References 25 publications
14
172
4
8
Order By: Relevance
“…The increased activity of MMP-2 in some (not all) macroscopically normal (control) supraspinatus is thought to represent evidence of an underlying pathological process, since histopathological studies have shown that degenerative change is common in cadaver supraspinatus tendons (Chard et al, 1994;Riley et al, 2001). Activity of MMP-2 and matrix degradation has also been reported in chronic ulcers (Wysocki et al, 1993), chronic wounds (Bullen et al, 1995) and atherosclerotic lesions (Li et al, 1996). We have also recently found up-regulation of MMP-2 gene expression in painful Achilles tendinopathy, and this activity was associated with high levels of matrix turnover as determined by pentosidine cross-link analysis (Ireland et al, 2001 and unpublished observations).…”
Section: Discussionmentioning
confidence: 60%
“…The increased activity of MMP-2 in some (not all) macroscopically normal (control) supraspinatus is thought to represent evidence of an underlying pathological process, since histopathological studies have shown that degenerative change is common in cadaver supraspinatus tendons (Chard et al, 1994;Riley et al, 2001). Activity of MMP-2 and matrix degradation has also been reported in chronic ulcers (Wysocki et al, 1993), chronic wounds (Bullen et al, 1995) and atherosclerotic lesions (Li et al, 1996). We have also recently found up-regulation of MMP-2 gene expression in painful Achilles tendinopathy, and this activity was associated with high levels of matrix turnover as determined by pentosidine cross-link analysis (Ireland et al, 2001 and unpublished observations).…”
Section: Discussionmentioning
confidence: 60%
“…High gelatinase activity has been described in chronic wounds, 13,36,37 which may be enhanced by low levels of active MMP inhibitors in these wounds. 36 MMP-2 does not appear to play a major role in the normal wound-healing process, as MMP-2-deficient mice display similar rates of wound re-epithelialization, granulation tissue formation, and collagen content. 38 However, high MMP-2 levels are found in chronic wounds.…”
Section: Neutrophil-derived Proteasesmentioning
confidence: 99%
“…Among others, markers downstream of the Wnt signaling pathway (e. g. elevated expression of nuclear β -catenin and c-myc [ 44 ] ), epidermal stem cell markers (e. g. decreased expression of leucine-rich repeats and immunoglobulin-like domain-containing protein 1 [LRIG 1] and keratin 15 [K15]), members of the TGF β superfamily (e. g. decreased expression of the bone morphogenetic protein receptor [BMPR] and TGF β I and II ligands), immunomodulatory proteins (e. g. decreased expression GATA-binding protein 3 (GATA3) and of inhibitors of DNA-binding proteins 2 and 4 (ID2 and ID4) [ 44,59 ] ), as well as antimicrobial peptides (e. g. decreased expression of cathelicidin [ 60 ] ) have been shown to be clinically associated with impaired healing in patients with chronic wounds. On the other hand, wound fl uid markers have also been identifi ed, including increased expression of metalloproteinases (e. g. MMP-1, 2, 3, 7, 8, 9, 10, 11, 13), decreased expression of their inhibitors (e. g. TIMP-1) [61][62][63] , increased IL-1 and IL-6 [ 64 ] levels, as well as decreased levels of albumin and total protein [ 65 ] . Systemic biomarkers associated with a high risk of developing chronic wounds have also been reported, with chronic ulcer patients showing high serum levels of procalcitonin [ 66 ] as well as MMP3 and 2 [ 67 ] , and a reduced number of CD34+/CD45-dim circulating cells [ 68 ] and micro RNAs such as miRNA-200b and miRNA-191 [ 69 ] .…”
Section: Potential Biomarkers Of Impaired Wound Healingmentioning
confidence: 99%